2021
DOI: 10.1590/interface.210399
|View full text |Cite
|
Sign up to set email alerts
|

Living Senior Labs, ecosistemas de co-creación e innovación abierta con personas mayores: revisión sistemática de la literatura en Ciencias Sociales

Abstract: Los Living Labs son experiencias colaborativas que buscan implicar a la ciudadanía en la gobernanza científica y la evaluación de tecnologías. A pesar de su interés, se sabe muy poco sobre estas comunidades, su funcionamiento, tipología y características. Por ello, se realizó una revisión sistemática de la literatura sobre de un tipo particular de Living Lab, orientado hacia las personas mayores: los Living Senior Labs. A partir de una búsqueda general en las principales bases de datos científicas (WOS y Scopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…Technological developments can help to improve the quality of life of older adults, but although the results of ongoing research are presented here, more data and results are needed to allow for an integral examination of the “technological senior.” To increase acceptance of these technologies, it is important and necessary for older adults to take in part in their design to show designers other purposes that were not planned (Fischer et al , 2021; Wanka and Gallistl, 2021; Naor et al , 2021). One resource that may allow for achievement of this objective is senior living labs, initiatives that are yielding highly positive results (Martín-García et al , 2021a). A senior living lab, enable older adults to take part in a co-creation process for devices and appliances adapted to their needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technological developments can help to improve the quality of life of older adults, but although the results of ongoing research are presented here, more data and results are needed to allow for an integral examination of the “technological senior.” To increase acceptance of these technologies, it is important and necessary for older adults to take in part in their design to show designers other purposes that were not planned (Fischer et al , 2021; Wanka and Gallistl, 2021; Naor et al , 2021). One resource that may allow for achievement of this objective is senior living labs, initiatives that are yielding highly positive results (Martín-García et al , 2021a). A senior living lab, enable older adults to take part in a co-creation process for devices and appliances adapted to their needs.…”
Section: Discussionmentioning
confidence: 99%
“…Gerontechnology (gerontology + technology) is an interdisciplinary research field applicable to gerontology and technology. It also includes the development and distribution of technology environments, products and services (Bouma and Graafmans, 1992; Martín-García et al , 2021a, 2021b, 2021c) to improve the daily lives and aging of older people with technology developments). Based on a report entitled “Technology for Adaptive Aging” by the US National Research Council (2003), literature consistently points out (Chen and Chan, 2014; Pew and Van Hemel, 2004; Martín-García, 2021b) that these technology environments, products and services are divided into five areas of development called “life domains”: Living Environments; Communication; Personal mobility and transportation; Health; and Employment, Education, Recreation or self-fulfillment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These results back up prior research that has identified barriers related to economic level, education, user experience, and usability problems, as well as anxiety or low perceived self-efficiency, or distrust and risk related to privacy and intimacy [ 50 , 51 ]. Barriers that lead to the cyber exclusion of this age group are especially important [ 52 ], so it is necessary to rely on mechanisms that minimize these barriers, such as digital literacy and initiatives such as Senior Living Lavs, which allow older adults to participate in a process of co-creation of devices and applications adapted to their needs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, favorece a los nuevos ecosistemas de co-creación apoyado en redes sociales (González et al, 2017) o los "Living senior Labs" que básicamente son experiencias colaborativas cuya finalidad es vincular nuevos actores en este caso personas mayores con mayor nivel de experticia (Martín et al, 2021), y la innegable relación con la gestión del conocimiento con la innovación en las organizaciones contemporáneas, soportando que las organizaciones no dependen exclusivamente de sus propios conocimientos, sino de la experticia de personas externas y aprovechar en conjunto el conocimiento (Millán et al, 2019;Pineda, 2019).…”
Section: Innovación Abierta En Colombiaunclassified